Alteration in 11 Beta-Hydroxysteroid Dehydrogenase Type-2 (HSD11B2) Gene as A Potential Candidate Parameter for Early Detection of Intrauterine Growth Restriction (IUGR) Events - Louis Fabio Jonathan Jusni; Patricia Patricia; Brigitte Leonie Rosadi (Molecular and Cellular Biomedical Sciences, 2021)
Intrauterine Growth Restriction (IUGR) incidence in Indonesia ranks in the top 10 of the highest in Asia. It is the main perinatal death cause. IUGR also impairs fetal neurodevelopment, which can affect the development of children until later ages. Lack of 11β-hydroxysteroid dehydrogenase type-2 (11β-HSD2) enzyme is influenced by changes in the coding gene, HSD11B2, one of IUGR's causes. The main diagnostic method of IUGR at this time is by using Doppler ultrasound. However, Doppler ultrasound has several limitations as many cases are not detected. Its clinical predictive value in various women is poor, as Doppler ultrasound is not recommended for use in the first trimester, detection of abnormalities in the second trimester seems to be too late for helpful interventions. The study aim is to present an overview concerning HSD11B2 gene alteration in an non-invasive prenatal testing (NIPT) as a possible diagnostic parameter for early detection in IUGR infants. This literature review is based on selected articles and studies taken from the Pubmed, Proquest, and EBSCO databases. A total of 4 studies reported the tendency for DNA methylation and decreased expression of the HSD11B2 gene in IUGR cases. Changes in the HSD11B2 gene have the potential to become a diagnostic parameter in the early detection of infants with IUGR. Further study and investigation of this possibility are needed.Keywords: intrauterine growth restriction, HSD11B2, early detection, diagnostic, non-invasive prenatal testing